Complex interactions between day length and diurnal patterns of gene expression drive photoperiodic responses in a perennial C4 grass. (1st April 2019) - Weng, Xiaoyu; Lovell, John T.; Schwartz, Scott L.; Cheng, Changde; Haque, Taslima; Zhang, Li; Razzaque, Samsad; Juenger, Thomas E.
Abstract: Photoperiod is a key environmental cue affecting flowering and biomass traits in plants. Key components of the photoperiodic flowering pathway have been identified in many species, but surprisingly few studies have globally examined the diurnal rhythm of gene expression with changes in day length. Using a cost‐effective 3′‐Tag RNA sequencing strategy, we characterize 9, 010 photoperiod responsive genes with strict statistical testing across a diurnal time series in the C4 perennial grass, Panicum hallii . We show that the vast majority of photoperiod responses are driven by complex interactions between day length and sampling periods. A fine‐scale contrast analysis at each sampling time revealed a detailed picture of the temporal reprogramming of cis ‐regulatory elements and biological processes under short‐ and long‐day conditions. Phase shift analysis reveals quantitative variation among genes with photoperiod‐dependent diurnal patterns. In addition, we identify three photoperiod enriched transcription factor families with key genes involved in photoperiod flowering regulatory networks. Finally, coexpression networks analysis of GIGANTEA homolog predicted 1, 668 potential coincidence partners, including five well‐known GI‐interacting proteins. Our results not only provide a resource for understanding the mechanisms of photoperiod regulation in perennial grasses but also lay a foundation to increase biomass yield in biofuel crops. Abstract : Dynamic gene expression under changing day length is critical for plants to optimize biomass production and reproductive fitness. Our study demonstrates that the vast majority of photoperiod responses are driven by complex interactions between photoperiod and diurnal patterns of gene expression, resulting in dynamic reprogramming of regulatory networks and biological processes in Panicum hallii . Key components of the photoperiodic flowering pathway have been identified in this emerging C4 bioenergy model for perennial grasses. Further, our study suggests that coincidence of critical day length recognition for the expression of key genes could be a universal mechanism controlling photoperiodic flowering and related physiological processes in plants.